2014
DOI: 10.1039/c4cy00639a
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of diols by gas-phase dehydrogenation and dehydration reactions on bifunctional Cu-based oxides

Abstract: A bifunctional ZCuMgAl (Z = 0.3–61.2 wt.% Cu) catalyst converts biomass-derived diols into valuable hydroxyketones or saturated and unsaturated ketones and alcohols depending on the Cu loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…1 correspond to Cu 2+ → Cu 0 reduction [29]. The dispersion (D) values were comparable to those reported for comparable Cu-based oxides [8,10,30,31].…”
Section: Catalyst Characterizationsupporting
confidence: 76%
See 1 more Smart Citation
“…1 correspond to Cu 2+ → Cu 0 reduction [29]. The dispersion (D) values were comparable to those reported for comparable Cu-based oxides [8,10,30,31].…”
Section: Catalyst Characterizationsupporting
confidence: 76%
“…Furthermore, we found that gas-phase reduction of ␣,␤-unsaturated ketones by hydrogen transfer reactions selectively forms saturated ketones on these catalysts [9]. We reported also that these materials promote the upgrading of polyols to valuable oxygenates by dehydrogenation and/or dehydration reactions, depending on the copper loading [10]. Recently, other researchers have shown that similar Cu-Mg-Al mixed oxides are suitable catalysts for C C coupling of methanol and ethanol [11], aqueous-phase upgrading of bio-oil [12], total oxidation of methane [13] and synthesis of 1,2-propanediol from glycerol [14] among many other applications.…”
Section: Introductionmentioning
confidence: 89%
“…Cu 0 reduction [26]. The 8.0CuMgAl sample reduced giving a single and broad reduction peak at around 550-600 K with a temperature at peak maximum (T M ) of 571 K. Similarly, sample 8.5CuSi showed also a broad peak with a T M value of 532 K, a value closer to that of Top Catal pure reference CuO (502 K) [10]. The differences in reducibility of both samples is assigned to the different preparation procedures and the resulting chemical environments of the copper species.…”
Section: Catalyst Characterizationmentioning
confidence: 61%
“…Details are described in [10,18]. In the TPR experiments, a reducing mixture of 5 % H 2 /Ar at a flow rate of 50 cm 3 /min was used; the reactor was loaded with a molar amount of copper (150 lmol) so that to meet the criteria of Monti et al [19] and Malet et al [20].…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation